ANALISIS KESADARAN GENERASI MUDA INDONESIA DALAM DUNIA POLITIK - Denis Irwandi, Muhamad; Akbar, Randika; Santa, Rahmat (Jurnal Sosio dan Humaniora (SOMA), 2023)
The role of human resources (HR) in politics and human resource management (HRM), as well as the importance of community participation, especially the younger generation, in the political process to secure their voices and interests. We explain political views from the perspective of Aristotle and Prof. Miriam Budiarjo, who stated politics as an effort to achieve the common good and set goals and achieve them. Today's young generation tends to reject politics because of the existence of deviations and bad political practices in Indonesia. In fact, their participation is very important for the future of democracy and sustainable development. This study uses a qualitative descriptive approach to describe the involvement of the younger generation in politics. We analyze people's political participation in the context of the role of political parties and how political education can increase the political awareness of the younger generation. The results of the research show that the younger generation has a crucial role in building a strong democracy and ensuring their active participation in building a better future for the nation. Therefore, political education for young people is an important step in creating a strong democracy and ensuring the active participation of the younger generation in building a better future for the nation, even though the role of social media as a tool to participate in politics is not yet fully effective.